Grasping of Real-World Objects Is Not Biased by Ensemble Perception - Fan, Annabel Wing-Yan; Guo, Lin Lawrence; Frost, Adam; Whitwell, Robert L.; Niemeier, Matthias; Cant, Jonathan S. (Frontiers in Psychology, 2021)
The visual system is known to extract summary representations of visually similar objects which bias the perception of individual objects toward the ensemble average. Although vision plays a large role in guiding action, less is known about whether ensemble representation is informative for action. Motor behavior is tuned to the veridical dimensions of objects and generally considered resistant to perceptual biases. However, when the relevant grasp dimension is not available or ambiguous ensemble perception may be informative to behavior by providing gist information about surrounding objects. In the present study, we examined if summary representations of a surrounding ensemble display influenced grip aperture and orientation towards a central circular target which had an explicit size but importantly no explicit orientation that the visuomotor system could selectively attend to. Maximum grip aperture and grip orientation were not biased by ensemble statistics during grasping, despite participants being able to perceive and provide manual estimations of ensemble characteristics. Support vector machine classification of ensemble statistics achieved above-chance classification accuracy when trained on kinematic and electromyography data of the perceptual but not grasping conditions, supporting our univariate findings. These results suggest that even along ambiguous grasping dimensions, visually-guided behaviors towards real-world objects are not biased by ensemble processing.